O uso do Whatsapp como ferramenta para o desenvolvimento da habilidade comunicativa em inglês como língua estrangeira em um contexto de Blended Learning - Severo, Suzan Severo de (Universidade do Vale do Rio dos Sinos, 2017)
This study was developed in a blended learning context in which there was an experiment on using WhatsApp, a largely used and well known tool for communication, as a means for fostering spontaneous dialogues among learners of English as a foreign language. Based on a sociocultural perspective and considering that learning happens through interaction mediated by sociocultural artifacts (Vygotsky, 1978), this work aims at understanding how the process of learning is mediated as students chat on WhatsApp. More specifically, it aims at analyzing students’ production of the foreign language as they interact using the language they learn through the group on WhatsApp and how it could, in some way, contribute with their learning process. Based on the data and the students’ opinions, it was found that WhatsApp can be an effective resource to engage students in producing the language they learn so that they have more opportunities for hypothesis testing, noticing gaps in their knowledge of the foreign language as well as engage them in metatalk (SWAIN,1985,1995,2005). Moreover, through their chatting, it was possible to notice that learners scaffolded each other and searched for means of maintaining themselves engaged in the dialogue by searching words in online dictionaries, using the first language as a support or using conversational tactics for negotiating meaning (LONG, 1983, 1996), what allowed students to get engaged in conversations and ile maintaining themselves engaged in conversations and both ask for and give support on the process of producing and learning the foreign language.
Keywords: Blended Learning; WhatsApp; Aprendizado de língua estrangeira; Teoria sociocultural; Language learning; Sociocultural theory; ACCNPQ::Lingüística, Letras e Artes::Lingüística